Atypical Granulomatosis with Polyangiitis Presenting with Meibomitis, Scleritis, Uveitis and Papillary Bladder Tumor: A Case Report and Literature Review - Takashi Kojima; Murat Dogru; Eisuke Shimizu; Hiroyuki Yazu; Aya Takahashi; Jun Shimazaki (Diagnostics, 2021)
Granulomatosis with polyangiitis (GPA) presents with a variety of systemic findings, sometimes with ocular findings initially, but is often difficult to diagnose at an early stage. An 85-year-old male had complaints of ocular dryness and redness and was diagnosed with meibomian gland dysfunction with meibomitis. Despite an initial treatment with topical steroid and antibiotics, the meibomitis did not improve and the left eye developed scleritis and iridocyclitis. The patient was administered topical mydriatics and oral steroids. During follow-up, the patient developed left hearing difficulty and reported a darker urine. Urinalysis revealed microscopic hematuria. A blood test showed an elevated erythrocyte sedimentation rate, positivity for perinuclear anti-neutorophil cytoplasmic antibody, and elevations in blood urea nitrogen and serum creatinine. Nasal mucosal biopsy showed a non-necrotizing granulomatous inflammation. Renal biopsy revealed focal glomerulosclerosis. Cystoscopy and bladder wash followed by a planned transurethral resection revealed atypical cells and apical papillary tumors which were resected. Iridocyclitis and scleritis responded well to oral prednisolone with 0.1% topical betamethasone and prednisolone ointment. The patient is tumor free with no recurrences 24 months after resection. GPA may present atypically with meibomian gland dysfunction without showing representative clinical findings. Early detection and treatment are essential for visual recovery.